Outcomes of Resection Surgery in Corrosive Esophageal Stricture - Hafsa Ijaz, Saad Arshad, Uzair Ahmed Qureshi, Muhammad Azam Tayyab, Abdul Rehman Alvi, Imran Ameen, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Esophageal stricture is a rarely encountered but a significant issue of worry throughout the world. Treatment options for esophageal stricture include endoscopic dilatation and surgery along with proton pump inhibitors. Surgery is performed if there is failure of enough dilatation and if recurrence occurs despite multiple dilatations. Objective: This study was designed to determine the outcome of resection surgery in adult patients presenting with Corrosive Esophageal Strictures. Material and Methods: A descriptive cross sectional study was carried out at surgery department, DHQ hospital Gujranwala, from December 2019 to June 2020. 60 consecutive patients, of age 20-60 years of either gender with presence of esophageal strictures caused by intake of corrosive substances and failed to undergo endoscopic dilatation due to difficulty in passing endoscope across the esophageal stricture, were included in the study. All study participants underwent resection surgery procedure under general anesthesia by a single surgical team. The marginal arcade alongside colon was conserved in all cases in which colon was utilized. Feeding jejunostomy was placed in all patients. Duration of surgery was noted. After surgery, patients were followed-up in surgical wards for 48 hours and examined on ultrasound for cervical anastomotic leak. Then patients were followed-up in OPD for 15 days and if dysphagia reoccurred, it was also noted. Results: The mean age of patients was 31.80 ± 7.74 years. There were 47(78.3%) male and 13(21.7%) female cases. There were 33.3% case who took acid, 16.7% took alkalis, 16.7% cases ingested metal salts, 21.7% had formalin, 6.7% cases had iodine tincture and 5.0% cases had other types of corrosive material. The mean operative time was 3.80 ± 0.80 hours. There were 11(18.3%) cases who had cervical anastomotic leak and 10(16.7%) cases had dysphagia related problem. No statistically significant difference (p≥0.05) was found in the outcomes of resection surgery across various groups based on age, gender, BMI, duration of corrosive intake, and type of corrosive substance ingested. Also, No significant difference (p≥0.05) was found in mean operative time in any stratum. Conclusion: It is concluded that outcome of resection surgery in adult patients presenting with Corrosive Esophageal Strictures was favorable with less complications. Hence these cases can be managed with standard surgical procedure to save their life and improve the quality of life. Keywords: Corrosives, Esophageal Stricture, Resection Surgery, Dysphagia, Cervical Anastomotic leak